A Novel Long-range Excitatory Neural Circuit from the Magnocellular Red Nucleus to Spinal Dorsal Horn Facilitates Neuropathic Pain-like Behaviors in Male Mice - Jiali Shi; Yinfeng Yuan; Yuhao Luo; Yue Guo; Jiashu Lian; Lin Lin; Danni Chen; Qian Wang; Xiumin Xue; Zhichao Chen; Yongjie Wang; Zhihui Huang (Neuroscience Bulletin, 2026)
Neuropathic pain arises from a primary lesion or disease affecting the somatosensory system; however, the brain circuitry underlying the regulation of neuropathic pain remains unclear. The red nucleus (RN) is a critical brain region involved in regulating muscle tension, coordinating movement, and facilitating sensorimotor integration. While some evidence has shown that RN regulates pain, its specific role in neuropathic pain and associated neural circuits remains elusive. In this study, we found that CaMKIIα-positive neurons in the magnocellular red nucleus (RMC CaMKIIα ) were activated following common peroneal nerve (CPN) ligation-induced chronic neuropathic pain in adult male mice. Interestingly, chemogenetic and optogenetic inhibition of these RMC CaMKIIα neurons alleviated the thermal hyperalgesia and mechanical allodynia in the neuropathic pain model mice, whereas activation of these neurons sufficiently induced the mechanical allodynia and thermal hyperalgesia in naïve mice. Trans-synaptic viral tracing studies further revealed that long-range CaMKIIα + neuron projections from RMC to the dorsal horn (DH) facilitated the neuropathic pain-like behaviors following CPN ligation. DH neurons received direct innervation from RMC CaMKIIα neurons, and inhibition of RMC CaMKIIα -DH CaMKIIα circuits alleviated the neuropathic pain in the ligated mice. Taken together, these results identify a novel long-range excitatory neural circuit from RMC to DH that facilitates the neuropathic pain-like behaviors in adult male mice, providing a new target for neuropathic pain treatment.